Carbon dioxide mineralization solid waste porous phase change material and preparation method and application thereof
Patent Information
- Application Number
- CN202611074090.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-16
AI Technical Summary
[0002]现有二氧化碳矿化多以封存量为核心指标,产物多为致密碳酸盐粉体或骨料,例如粉煤灰、钢渣等工业固废多以直接掺混或高温处理方式利用,其内部孔结构不可设计,热调节、储能等功能难以引入,只能提升少量比热,未形成结构级功能材料,仅作为低值填料使用,固废资源化路径附加值低,无法形成具有明确功能价值的终端产品,难以抵消矿化过程的能耗与设备成本,导致大规模应用受限
1、本申请提供了一种孔结构可控的原位矿化方法,通过调控反应条件直接在固废微粉上形成高孔隙率、连通孔、泡沫样碳酸盐骨架,无需高温煅烧;利用多孔骨架+亲/疏水处理配合真空/毛细力浸渍,确保相变材料(PCM)高负载且孔内包裹稳固,减少循环泄漏;通过一体化封装结构,在浸渍后进行微孔封闭,兼顾热性能与力学/防火。
Smart Images

Figure CN122916489A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of carbon dioxide mineralization technology, and specifically relates to a porous phase change material for carbon dioxide mineralization solid waste, its preparation method and application. Background Technology
[0002] Current carbon dioxide mineralization methods primarily focus on the amount of carbon dioxide stored as the core indicator, and the products are mostly dense carbonate powders or aggregates. For example, industrial solid wastes such as fly ash and steel slag are often utilized through direct blending or high-temperature treatment. Their internal pore structure cannot be designed, and functions such as thermal regulation and energy storage are difficult to introduce. They can only increase specific heat slightly and have not formed structural functional materials. They are only used as low-value fillers. The added value of the solid waste resource utilization path is low, and it is impossible to form end products with clear functional value. It is difficult to offset the energy consumption and equipment costs of the mineralization process, which limits large-scale application.
[0003] Current applications of phase change materials (PCMs) face an engineering dilemma: high latent heat versus reliability. PCMs are prone to leakage and exhibit significant volume variations; traditional microcapsule or simple adsorption methods have limited loading capacities; and high PCM content can lead to decreased material strength and deteriorated fire resistance. Therefore, in the construction field, PCM applications are largely confined to experimental or small-scale demonstrations, lacking stable and engineerable carrier structures. Therefore, it is necessary to provide a porous phase change material for carbon dioxide mineralization of solid waste, its preparation method and application. Under low energy consumption conditions, industrial solid waste is transformed into a porous carbonate framework with a designable pore structure through in-situ CO2 mineralization, and used as a carrier of highly stable phase change material to prepare building functional panels that combine carbon sequestration, thermal regulation and engineering reliability. Summary of the Invention
[0004] To address the aforementioned problems, this application provides a method for preparing porous phase change materials from carbon dioxide mineralized solid waste, comprising: Solid waste powder is suspended in water and then mixed with alkaline solution to form a slurry. Porous structures can be constructed by adding a template agent to the slurry or by degassing it. CO2 is introduced into the slurry to form a porous precipitate, yielding mineralized products; The mineralized products are dried and shaped to obtain a mineralized framework; A modified framework is obtained by adjusting the pore structure and surface modification of the mineralized framework. After vacuum treatment, the modified skeleton is sequentially filled with phase change material and surface encapsulated to obtain a porous phase change material.
[0005] Furthermore, the mass ratio of solid waste powder to water is (20-60):100, the solid waste powder is fly ash, steel slag, or limestone tailings with a D50 particle size of 5-40 micrometers, and the specific surface area of the solid waste powder is 300-500 m². 2 / kg.
[0006] Furthermore, the alkaline solution is an alkaline solution containing calcium or magnesium ions, with a concentration of calcium or magnesium ions of 0.5-2 mol / L, and the mass ratio of the solute in the alkaline solution to the mass of the solid waste powder is (0.2-0.8):1.
[0007] Furthermore, the stencil agent includes starch or gelatin, and the mass ratio of the stencil agent to the slurry is (0-30):100.
[0008] Further, the degassing process is characterized by including: Add 0.1-1.0 wt% of foam stabilizer to the slurry, then pressurize it to 0.1-0.3 MPa under closed conditions by introducing nitrogen gas while stirring for 10-20 min, and then depressurize it to atmospheric pressure within 1-3 s.
[0009] Furthermore, CO2 is introduced into the slurry to form a porous precipitate, including: The rate at which CO2 is introduced per liter of slurry is controlled to be 0.1-2.0 L / min; During the reaction, the pH of the reaction system was maintained at 8.5-10.5 by adding NaOH solution with a concentration of 1-5 mol / L; The initial nucleation temperature is controlled at 20-30℃, and then the temperature is increased to 60-80℃ at a rate of 1-5℃ / min and held at that temperature for 1-2 hours. For the first 15-30 minutes after introducing CO2, mechanically stir at 800-1200 rpm. Once the solution becomes turbid, mechanically stir at 150-300 rpm.
[0010] Furthermore, pore structure adjustment includes: etching the mineralized framework with a weak acid, and removing reaction byproducts from the surface of the mineralized framework with water or a weak base. The mineralized framework is then kept at a temperature of 150-300℃.
[0011] Furthermore, surface modification treatments include surface modification of the mineralized framework using silane coupling agents or hydrophobic / oleophilic coatings.
[0012] Furthermore, the vacuum treatment includes placing the modified skeleton in a vacuum environment of 10-50 mbar for 15-60 minutes to remove air from the modified skeleton.
[0013] Furthermore, the phase change material includes at least one of paraffin, fatty acid ester, PEG and inorganic salt hydrate, the melting point of the phase change material is 18-30℃, and after the phase change material is filled, the mass ratio of the phase change material to the modified skeleton is (40-70):(30-60).
[0014] Furthermore, surface encapsulation includes coating the outer surface of the modified skeleton after filling with phase change material with a 0.1-1 mm epoxy resin or polyurethane coating.
[0015] This application also discloses a porous phase change material for carbon dioxide mineralization solid waste, which is prepared using the above-described preparation method.
[0016] This application also discloses an application of a porous phase change material for carbon dioxide mineralized solid waste, wherein the aforementioned porous phase change material for carbon dioxide mineralized solid waste is compositely bonded with an insulation layer and / or a reinforcing layer to prepare building panels.
[0017] Compared with the prior art, this application has the following advantages: 1. This application provides an in-situ mineralization method with controllable pore structure, which directly forms a high-porosity, interconnected, foam-like carbonate framework on solid waste powder by controlling reaction conditions, without the need for high-temperature calcination; by using a porous framework + hydrophilic / hydrophobic treatment combined with vacuum / capillary impregnation, the phase change material (PCM) is ensured to have high load and stable encapsulation within the pores, reducing circulation leakage; through an integrated encapsulation structure, the micropores are sealed after impregnation, taking into account both thermal performance and mechanical / fireproof properties.
[0018] 2. The process described in this application can be used for co-production with power plants and cement plants within building material plants, reducing transportation and processing costs, and realizing the resource utilization of solid waste, long-term mineralization and storage of CO2, and building energy conservation.
[0019] Other features and advantages of this application will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the application. The objectives and other advantages of this application may be realized and obtained by means of the structures pointed out in the description, claims and drawings. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 A flowchart illustrating a method for preparing a porous phase change material from carbon dioxide mineralized solid waste according to an embodiment of this application is shown. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0023] like Figure 1 As shown, this application provides a method for preparing porous phase change materials from carbon dioxide mineralization solid waste, comprising: Solid waste powder is suspended in water at a mass ratio of (20-60):100. Then, an alkaline solution is added to prepare a slurry, with a solute-to-solid waste powder mass ratio of (0.2-0.8):1. The solid waste powder consists of fly ash, steel slag, or limestone tailings with a D50 particle size of 5-40 micrometers and a specific surface area of 300-500 m². 2 / kg, the alkaline solution is an alkaline solution containing calcium or magnesium ions, with a concentration of 0.5-2 mol / L. It should be noted that solid waste powder particles larger than 40 micrometers will result in extremely poor calcium / magnesium ion dissolution kinetics, failing to provide sufficient reactants. Particles smaller than 5 micrometers are prone to severe agglomeration, hindering subsequent CO2 mass transfer and preventing in-situ mineralization within the agglomerates, thus failing to form a uniform framework. Optionally, during the slurry preparation stage, 0.1-1.5% of nano-calcium carbonate (particle size 50-100 nm) can be added as seed crystals, or 0.01-0.05 mol / L of amino acid surfactants (such as L-aspartic acid or glutamic acid) can be added. Optionally, 0.1-1.0 mol / L of sodium chloride or potassium chloride can be added to the slurry to adjust the ionic strength of the solution, thereby changing the activity coefficient of calcium carbonate precipitation and promoting the formation of porous aragonite or spheroidal phases.
[0024] A porous structure is constructed by adding a template agent or performing degassing treatment on the slurry. The template agent includes starch or gelatin, and the mass ratio of the template agent to the slurry is (0-30):100. The degassing treatment includes adding 0.1-1.0 wt% of a foam stabilizer (such as sodium dodecyl sulfate SDS) to the slurry, followed by pressurizing to 0.1-0.3 MPa under sealed conditions while stirring for 10-20 min, and then depressurizing to atmospheric pressure within 1-3 s. By controlling the degassing pressure difference and the concentration of the foam stabilizer, the pore size can be controlled between 10-500 micrometers.
[0025] The process involves introducing CO2 into the slurry to form a porous precipitate and obtain mineralized products. This includes: controlling the CO2 introduction rate at 0.1-2.0 L / min per liter of slurry; maintaining the pH of the reaction system at 8.5-10.5 by adding a 1-5 mol / L NaOH solution during the reaction; controlling the initial nucleation temperature at 20-30℃, and then raising the temperature to 60-80℃ at a rate of 1-5℃ / min and holding it at that temperature for 1-2 hours; mechanically stirring at 800-1200 rpm for the first 15-30 minutes after introducing CO2, and then mechanically stirring at 150-300 rpm after the solution becomes turbid.
[0026] The mineralized products are dried and shaped to obtain a mineralized framework.
[0027] A modified framework is obtained by adjusting the pore structure and modifying the surface of the mineralized framework. The pore structure adjustment includes: etching the mineralized framework with a weak acid (e.g., a 0.1-0.5 mol / L acetic acid solution); removing reaction byproducts from the surface of the mineralized framework with water or a weak base (e.g., a 0.05-0.2 mol / L sodium bicarbonate solution); and then heating the mineralized framework at 150-300°C to remove the template agent and dry it. If no template agent is added, heating is only used for drying. Surface modification treatment involves surface modification of the mineralized framework using silane coupling agents or hydrophobic / oleophilic coatings. The specific process is as follows: the mineralized framework is placed in anhydrous ethanol or a water / ethanol mixture (water to ethanol volume ratio of 5-30:70-95) containing 1-5 wt% silane coupling agent (such as Dynasylan OCTEO and Dynasylan AMEO produced by Evonik Industries) or a hydrophobic / oleophilic coating (such as DOWSIL184 silicone elastomer produced by Dow Chemical). The mixture is mechanically stirred or ultrasonically treated at 25-50°C for 1-4 hours to allow the silane coupling agent or hydrophobic / oleophilic coating to undergo a condensation reaction with the hydroxyl groups on the surface of the mineralized framework. Subsequently, the surface is dried and cured at 80-120°C for 2-4 hours to complete the surface grafting. The surface of the mineralized framework is treated with silane coupling agents or hydrophobic / oleophilic coatings to make it compatible or hydrophobically matched with the selected PCM, reducing the conflict between the PCM and moisture and improving the impregnation efficiency. Optionally, before adjusting the pore structure of the mineralized framework, the mineralized framework can be aged for 24-72 hours under a humidity of 90-95%RH. Further crystal bonding can improve mechanical strength. This humidity range can ensure the presence of a water film on the surface of carbonate crystals, which is beneficial to the growth of seed crystals and the strengthening of the structure.
[0028] After vacuum treatment, the modified skeleton is sequentially filled with phase change material and then surface-encapsulated to obtain a porous phase change material. Vacuum treatment includes placing the modified skeleton in a vacuum environment of 10-50 mbar for 15-60 min to remove air from the skeleton. The phase change material includes at least one of paraffin wax, fatty acid esters, PEG, and inorganic salt hydrates, with a melting point of 18-30℃. After filling, the mass ratio of phase change material to modified skeleton is (40-70):(30-60). Surface encapsulation includes coating the outer surface of the modified skeleton with a 0.1-1 mm layer of epoxy resin or polyurethane.
[0029] This application also discloses a porous phase change material for carbon dioxide mineralization solid waste, which is prepared using the above-described preparation method.
[0030] This application also discloses an application of a porous phase change material for carbon dioxide mineralized solid waste, wherein the aforementioned porous phase change material for carbon dioxide mineralized solid waste is compositely bonded with an insulation layer and / or a reinforcing layer to prepare building panels.
[0031] To better illustrate this solution, the following embodiments and comparative examples are provided.
[0032] Example 1 Fly ash (D50=5 micrometers) was suspended in water at a mass ratio of 20:100 to fly ash to water. Then, an alkaline solution (0.5 mol / L calcium hydroxide) was added to prepare a slurry, with a mass ratio of solute in the alkaline solution to fly ash of 0.2:1.
[0033] Without adding a template agent, CO2 was introduced into the slurry at a rate of 0.1 L / min. During the reaction, the pH of the reaction system was maintained at 8.5 by adding a 1 mol / L NaOH solution. A programmed temperature rise was used, with the initial nucleation temperature controlled at 20°C, then increased to 60°C at a rate of 1°C / min and held at that temperature for 1 hour. For the first 15 minutes after CO2 introduction, mechanical stirring was performed at 800 rpm. Once the solution became turbid, mechanical stirring was reduced to 150 rpm. The mineralized product was then dried and shaped to obtain the mineralized framework.
[0034] The pore structure of the mineralized framework was adjusted by etching it with a weak acid (acetic acid solution, 0.1 mol / L) and removing reaction byproducts from the surface using a weak base (sodium bicarbonate solution, 0.05 mol / L). The mineralized framework was then heated at 150 °C. Next, the mineralized framework was placed in an ethanol solution containing 2 wt% octyltriethoxysilane (Dynasylan OCTEO produced by Evonik Industries) and mechanically stirred at 25 °C for 2 hours. Finally, it was dried and cured at 100 °C for 2 hours to complete the surface grafting.
[0035] The modified skeleton was placed in a vacuum environment of 20 mbar for 15 min to remove the air inside the modified skeleton. The pressure difference drove the impregnation of liquid organic phase change paraffin RT28. 0.1 mm of E-44 epoxy resin was then coated on the outer surface of the modified skeleton after it was filled with phase change material.
[0036] Example 2 Steel slag powder (D50=20 micrometers) was suspended in water at a mass ratio of 40:100 to water. Then, an alkaline solution (calcium hydroxide with a concentration of 1 mol / L) was added to prepare a slurry, with the mass ratio of the solute in the alkaline solution to the mass ratio of the steel slag powder being 0.5:1.
[0037] Starch was added as a template agent, with a starch-to-slurry mass ratio of 15:100. CO2 was introduced into the slurry at a rate of 1 L / min. During the reaction, the pH of the reaction system was maintained at 9.5 by adding a 3 mol / L NaOH solution. A programmed temperature rise was used, with the initial nucleation temperature controlled at 25°C, and the temperature increased to 70°C at a rate of 3°C / min and held at that temperature for 1.5 hours. For the first 15 minutes after CO2 introduction, mechanical stirring was performed at 1000 rpm. After the solution became turbid, mechanical stirring was performed at 220 rpm. The mineralized product was dried and shaped to obtain the mineralized framework.
[0038] The pore structure of the mineralized framework was adjusted by etching it with a weak acid (acetic acid solution, 0.3 mol / L) and removing reaction byproducts from the surface using a weak base (sodium bicarbonate solution, 0.1 mol / L). The mineralized framework was then heated at 200°C to remove the template agent, releasing interconnected macropores. The mineralized framework was then placed in an ethanol solution containing 3 wt% polydimethylsiloxane (DOWSIL 184 silicone elastomer manufactured by Dow Chemical) and mechanically stirred at 35°C for 2 hours. Following this, it was dried and cured at 80°C for 3 hours to complete the surface grafting.
[0039] The modified skeleton was placed in a vacuum environment of 15 mbar for 45 min to remove the air inside the modified skeleton. The pressure difference drove the impregnation of liquid organic phase change paraffin RT28. The outer surface of the modified skeleton after filling with phase change material was coated with 0.5 mm of E-44 polyurethane.
[0040] Example 3 Limestone tailings (D50=40 micrometers) were suspended in water at a mass ratio of 60:100 to water. Then, an alkaline solution (calcium hydroxide with a concentration of 1 mol / L) was added to prepare a slurry, with the mass ratio of the solute in the alkaline solution to the mass of the limestone tailings being 0.8:1.
[0041] Gelatin was added as a template agent, with a gelatin-to-slurry mass ratio of 30:100. CO2 was introduced into the slurry at a rate of 2.0 L / min. During the reaction, the pH of the reaction system was maintained at 10.5 by adding a 5 mol / L NaOH solution. A programmed temperature rise was used, with the initial nucleation temperature controlled at 30°C, then increased to 80°C at a rate of 5°C / min and held at that temperature for 2 hours. For the first 30 minutes after CO2 introduction, mechanical stirring was performed at 1200 rpm. Once the solution became turbid, mechanical stirring was reduced to 300 rpm. The mineralized product was dried and shaped to obtain the mineralized framework.
[0042] The pore structure of the mineralized framework was adjusted by etching it with a weak acid (acetic acid solution, 0.5 mol / L) and removing reaction byproducts from the surface using a weak base (sodium bicarbonate solution, 0.2 mol / L). The mineralized framework was then heated at 300°C to remove the template agent, releasing interconnected macropores. The mineralized framework was then placed in an water / ethanol solution containing 5 wt% 3-aminopropyltriethoxysilane (Dynasylan AMEO from Evonik Industries) and mechanically stirred at 50°C for 3 hours. Finally, it was dried and cured at 120°C for 4 hours to complete the surface grafting.
[0043] The modified skeleton was placed in a 50 mbar vacuum environment for 60 min to remove the air inside the modified skeleton. Liquid calcium chloride hexahydrate was impregnated by pressure difference. A 1.0 mm layer of E-44 epoxy resin was then coated on the outer surface of the modified skeleton after it was filled with phase change material.
[0044] Example 4 Fly ash (D50=5 micrometers) was suspended in water at a mass ratio of 20:100 to fly ash to water. Then, an alkaline solution (0.5 mol / L calcium hydroxide) was added to prepare a slurry, with a mass ratio of solute in the alkaline solution to fly ash of 0.2:1.
[0045] Without adding a template agent, add 0.5 wt% sodium dodecyl sulfate (SDS) to the slurry, then pressurize it to 0.2 MPa under closed conditions by introducing nitrogen gas while stirring for 15 min, and then depressurize it to atmospheric pressure within 2 s.
[0046] CO2 was introduced into the slurry at a rate of 0.1 L / min. During the reaction, the pH of the reaction system was maintained at 8.5 by adding a 1 mol / L NaOH solution. A programmed temperature rise was used, with the initial nucleation temperature controlled at 20°C, then increased to 60°C at a rate of 1°C / min and held at that temperature for 1 hour. For the first 15 minutes after CO2 introduction, mechanical stirring was performed at 800 rpm. Once the solution became turbid, mechanical stirring was reduced to 150 rpm. The mineralized product was dried and shaped to obtain the mineralized framework.
[0047] The pore structure of the mineralized framework was adjusted by etching it with a weak acid (acetic acid solution, 0.1 mol / L) and removing reaction byproducts from the surface using a weak base (sodium bicarbonate solution, 0.05 mol / L). The mineralized framework was then heated at 150 °C. Next, the mineralized framework was placed in an ethanol solution containing 2 wt% octyltriethoxysilane (Dynasylan OCTEO produced by Evonik Industries) and mechanically stirred at 25 °C for 2 hours. Finally, it was dried and cured at 100 °C for 2 hours to complete the surface grafting.
[0048] The modified skeleton was placed in a vacuum environment of 20 mbar for 15 min to remove the air inside the modified skeleton. The pressure difference drove the impregnation of liquid organic phase change paraffin RT28. 0.1 mm of E-44 epoxy resin was then coated on the outer surface of the modified skeleton after it was filled with phase change material.
[0049] Comparative Example 1 Fly ash of equal particle size and calcium hydroxide are mixed directly at a mass ratio of 0.2:1, and CO2 is introduced for natural reaction to obtain dense phase carbonate powder. Then, it is directly mixed with molten RT28 paraffin by mechanical stirring and pressed into blocks.
[0050] Comparative Example 2 Using conventional building gypsum powder as the base material, 50wt% of commercially available paraffin microcapsule phase change material is directly added, mechanically mixed, and then pressed into blocks.
[0051] The materials from Examples 1-4 and Comparative Examples 1-2 were subjected to performance tests.
[0052] Compressive strength: The compressive strength of samples of the same size was determined using a computer-controlled universal testing machine in accordance with GB / T 17671 standard.
[0053] Phase change latent heat: Core samples were ground and their latent heat of fusion (J / g) was determined using a differential scanning calorimeter (DSC) at a heating rate of 5℃ / min within the range of 0-50℃.
[0054] Leakage rate after 50 thermal cycles: Place a sample of a specific size on qualitative filter paper, put it in a 50°C oven (above the melting point of paraffin / phase transition point of inorganic salts) and keep it at a constant temperature for 2 hours, then lower it to 20°C. Repeat this hot and cold cycle 50 times, weigh the difference in sample mass before and after the cycle, and calculate the percentage of leakage.
[0055] The test results are shown in Table 1. Examples 1-3 achieved precise surface chemical functionalization matching using Dynasylan OCTEO, DOWSIL 184, and Dynasylan AMEO, respectively. This resulted in a porous framework exhibiting strong interfacial affinity for both organic paraffins and inorganic hydrated salts. Combined with vacuum impregnation, the PCM mass ratio reached 42.5-68.5 wt%, and the leakage rate remained below 1.6% after 50 thermal cycles, completely solving the fatal flaw of poor adsorption and easy leakage (leakage rate 14.5%) of the traditional carbonization products in Comparative Example 1. While maintaining an extremely high latent heat of phase transition of 103.5-128.4 J / g, Examples 1-4 retained a compressive strength of 8.8-15.2 MPa thanks to the structural support of the three-dimensional interconnected carbonate framework generated by in-situ mineralization. In contrast, the traditional direct blending of high-content microcapsules (Comparative Example 2), while achieving a loading of 50 wt%, suffers a precipitous drop in structural strength (only 2.1 MPa, unsuitable for use as a sheet material), and the microcapsules are prone to rupture under stress, leading to secondary leakage. This application successfully achieves a triple balance of "high energy storage," "leakage prevention," and "high strength."
[0056] Table 1
[0057] Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.
Claims
1. A method for preparing a porous phase change material from carbon dioxide mineralized solid waste, characterized in that, include: Solid waste powder is suspended in water and then mixed with alkaline solution to form a slurry. A porous structure is constructed by adding a template agent to the slurry or by degassing it. CO2 is introduced into the slurry to form a porous precipitate, thereby obtaining a mineralized product; The mineralized product is dried and shaped to obtain a mineralized framework; The mineralized framework is subjected to pore structure adjustment and surface modification treatment to obtain a modified framework; After vacuum treatment, the modified skeleton is sequentially filled with phase change material and surface encapsulated to obtain a porous phase change material.
2. The preparation method according to claim 1, characterized in that, The mass ratio of the solid waste powder to water is (20-60):
100. The solid waste powder is fly ash, steel slag, or limestone tailings with a D50 particle size of 5-40 micrometers, and the specific surface area of the solid waste powder is 300-500 m². 2 / kg.
3. The preparation method according to claim 1, characterized in that, The alkaline solution is an alkaline solution containing calcium or magnesium ions, the concentration of which is 0.5-2 mol / L, and the mass ratio of the solute in the alkaline solution to the mass of the solid waste powder is (0.2-0.8):
1.
4. The preparation method according to claim 1, characterized in that, The template agent includes starch or gelatin, and the mass ratio of the template agent to the slurry is (0-30):
100.
5. The preparation method according to claim 1, characterized in that, The degassing process includes: Add 0.1-1.0 wt% of foam stabilizer to the slurry, then pressurize it to 0.1-0.3 MPa under closed conditions by introducing nitrogen gas while stirring for 10-20 min, and then depressurize it to atmospheric pressure within 1-3 s.
6. The preparation method according to claim 1, characterized in that, The process of introducing CO2 into the slurry to form a porous precipitate includes: The rate at which CO2 is introduced into each liter of the slurry is controlled to be 0.1-2.0 L / min; During the reaction, the pH of the reaction system was maintained at 8.5-10.5 by adding NaOH solution with a concentration of 1-5 mol / L; The initial nucleation temperature is controlled at 20-30℃, and then the temperature is increased to 60-80℃ at a rate of 1-5℃ / min and held at that temperature for 1-2 hours. For the first 15-30 minutes after introducing CO2, mechanically stir at 800-1200 rpm. Once the solution becomes turbid, mechanically stir at 150-300 rpm.
7. The preparation method according to claim 1, characterized in that, The pore structure adjustment includes: etching the mineralized framework with a weak acid, and removing reaction byproducts from the surface of the mineralized framework with water or a weak alkali. The mineralized framework is then heated at a temperature of 150-300℃.
8. The preparation method according to claim 1, characterized in that, The surface modification treatment includes surface modification of the mineralized framework using silane coupling agents or hydrophobic / oleophilic coatings.
9. The preparation method according to claim 1, characterized in that, The vacuum treatment includes placing the modified skeleton in a vacuum environment of 10-50 mbar for 15-60 minutes to remove air from the modified skeleton.
10. The preparation method according to claim 1, characterized in that, The phase change material includes at least one of paraffin, fatty acid ester, PEG and inorganic salt hydrate, the melting point of the phase change material is 18-30℃, and after the phase change material is filled, the mass ratio of the phase change material to the modified skeleton is (40-70):(30-60).
11. The preparation method according to claim 1, characterized in that, The surface encapsulation includes coating the outer surface of the modified skeleton with a 0.1-1 mm epoxy resin or polyurethane coating after filling with phase change material.
12. A porous phase change material for carbon dioxide mineralization solid waste, characterized in that, It is prepared by the preparation method according to any one of claims 1-11.
13. An application of a porous phase change material for carbon dioxide mineralization solid waste, characterized in that, Building panels are prepared by bonding the porous phase change material of carbon dioxide mineralized solid waste as described in claim 12 with an insulation layer and / or a reinforcing layer.